Pollinator ecology at a landscape scale - Hecq, Florence (Trinity College (Dublin, Ireland). Department of Botany, 2016)
Pollination is a key ecosystem service in natural and agricultural ecosystems which provides benefits to human society. It has been estimated that 87.5 % of angiosperms depend on animal pollinators. The role of pollinators in pollination processes is to pick-up, transfer and deposit viable pollen, this enables seed set and fruit development and reproduction in plants. The pollination process is essential not only for wild plants but also for cultivated plants. However, pollinators and the pollination services they provide are increasingly threatened by the pressures exerted by humans on the environment such as agricultural intensification leading to landscape change. It is within this context that my study aims to understand the effects of landscape and geographic location on pollinator diversity, abundance and the provision of pollination services. A range of different measures and methods were used to characterise the landscape, flower-visiting insect diversity and pollination services.
Keywords: Botany, Ph.D.; PhD Trinity College Dublin, 2016